Analisis Kualitas Produk Minyak Goreng Kemasan Standing Pouch (STP) Menggunakan Metode FMEA Pada PT. KIAS - Muhammad Ramadhan Fernandi; Akhmad Wasiur Risqi; Yanuar Pandu Negoro (Jurnal Serambi Engineering, 2022)
This study aims to determine product defects in the company PT. KIAS. This company joined the wings group and is engaged in food, namely the production of 1L and 2L STP (Standing Pouch) cooking oil packaging. factory location is located JL. Sukomulyo KM 24 Tenger Manyar Gresik. This research itself was carried out within a period of 1 month to be exact in March 2022. From the many defects in 1L and 2L packaged cooking oil products that occurred during production at PT. KIAS, for this reason in this study in order to be able to handle the problem of defects in the 1L and 2L packaged cooking oil products. From the results of data processing, there are more product defects in 1L cooking oil compared to 2L, this is because the machine used for 1L cooking oil can directly fill 2 at once. For this reason, this study analyzes the defects of 1L packaged cooking oil products using the FMEA method.